2016
DOI: 10.1111/emre.12079
|View full text |Cite
|
Sign up to set email alerts
|

The ‘CEO’ Effect on the Performance of Brazilian Companies: An Empirical Study Using Measurable Characteristics

Abstract: The experience and competence of CEOs may have a positive influence on the performance of firms. Using secondary data on the performance of 73 Brazilian listed companies and primary data collected through a survey of the social and demographic characteristics of CEOs we tested a set of hypotheses concerning the influence of CEOs on the performance of the firms they headed between 1997 and 2012. Specifically, we examined the relationships between CEOs’ experience and competence regarding common accounting indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 86 publications
4
15
0
4
Order By: Relevance
“…CEO insider has shown to have a positive relationship with both return on equity (ROE) and ROA. The positive correlation of CEO insider is not surprising in that Serra et al (2016) pointed out that a CEO with industry expertise may affect performance positively. Overall, the Pearson correlation shows that the overall experience is negatively correlated with firm performance in the financial sector.…”
Section: Correlation Matrixmentioning
confidence: 95%
“…CEO insider has shown to have a positive relationship with both return on equity (ROE) and ROA. The positive correlation of CEO insider is not surprising in that Serra et al (2016) pointed out that a CEO with industry expertise may affect performance positively. Overall, the Pearson correlation shows that the overall experience is negatively correlated with firm performance in the financial sector.…”
Section: Correlation Matrixmentioning
confidence: 95%
“…Barker and Mueller (2002) confirmed that there was a significant enhancement in R&D spending linked with a CEO possessing an undergraduate degree, but no significant impact was noticed for advanced levels of educational achievement. Likewise, CEO’s competence indicated that in firms where the CEO possesses better educational qualifications, there is no enhancement in performance (Serra, Três, & Ferreira, 2016). However, Farag and Mallin (2018) displayed that there is a very significant and positive association between CEO higher education estimated by CEOs who have degrees like MBA, MSc and PhD, and corporate risk taking.…”
Section: Related Literaturementioning
confidence: 99%
“…Second, from a theoretical and practitioner point of view, corporate governance is important in corporate decision‐making and thus, should and is expected to influence corporate outcomes (Larcker et al ., ; Foss and Stea, ). Indeed, this expectation is reflected in the large volume of studies that have investigated the effect of different corporate governance mechanisms on different managerial behaviour and corporate outcomes (e.g., Morck et al ., ; Yermack, ; Murphy, ; Gompers et al ., ; Donadelli et al ., ; Serra et al ., ; Granado‐Peiró and López‐Gracia, ). However and as corporate governance is a complex ‘concept' to operationalise, existing studies have either mostly employed single corporate governance mechanisms, such as board size and ownership structure (e.g., Morck et al ., ; Yermack, ) or some form of arbitrarily constructed composite governance disclosure indices (e.g., Gompers et al ., ; Bebchuk et al ., ; Karpoff et al ., ).…”
Section: Introductionmentioning
confidence: 99%